Physician Density and Infant Mortality: A Semiparametric Analysis of the Returns to Health Care Provision - Helge Liebert; Beatrice Mäder (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper investigates the effect of physicians on infant mortality, stillbirths and the incidence of common childhood diseases. We construct a new panel data set covering German municipalities from 1928 to 1936 based on historical sources. The endogeneity of health care supply is addressed by using the expulsion of Jewish physicians from health insurance schemes by the Nazi government in 1933 as a source of exogenous variation in regional physician density. The results indicate substantial mortality effects due to changes in physician density. One additional physician per 1,000 of population reduces infant mortality by 23% and stillbirths by 16%. We find similar negative effects for gastrointestinal diseases and the incidence of measles, influenza and bronchitis. To investigate diminishing returns to health care provision, we develop a semiparametric control function approach. Our results indicate that the marginal returns to physicians are highly nonlinear and decreasing.
Keywords: I10; I18; N34; 330; infant mortality; physicians; health care supply; childhood diseases; semiparametric IV